U.S. leadership, history, and bilateral relations in Northeast Asia - Rozman, Gilbert (Cambridge, U.K. : Cambridge University Press, 2011)
'This book explores the rising importance of history in reshaping international relations in Northeast Asia'--
'Whereas most discussions of history have centered on the rift between China and Japan, this book focuses on three other divisions stemming from deep-seated memories within Northern Asia, which increasingly will test U.S. diplomacy and academic analysis. The first division involves long-suppressed Japanese and South Korean memories that are critical of U.S. behavior -- concerning issues such as the atomic bombings, the Tokyo Tribunal, and the Korean War. How should the United States respond as these memories come out into the open, complicating vital bilateral alliances? The second division is the enduring disagreement between Japan and South Korea over history. What can the United States do to invigorate urgently needed trilateral ties? The third and most important division is the revival of a sinocentric worldview, which foretells a struggle between China and other countries concerning history, one that has already begun in China's dispute with South Korea and is likely to implicate the United States above all. Presenting three perspectives on each theme, the book launches a multi-sided discussion of the importance of history in international relations'--
Includes bibliographical references and index.
Keywords: Collective memory -- Political aspects -- East Asia; United States -- Foreign relations -- East Asia; East Asia -- Foreign relations -- United States; East Asia -- Foreign relations -- 20th century; East Asia -- Politics and government -- 20th century